Long-term Marginal Bone Stability in Atrophic Ridges Vertically Augmented with Guided Bone Regeneration: A Systematic Review - DeGuzman, John Paul. (Tufts University. Tisch Library., 2023)
Thesis (M.S.)--Tufts University, 2023.; Submitted to the Dept. of Periodontology.; Advisor: Yong Hur.; Committee: Yumi Ogata, Lorenzo Mordini, and Sarah Pagni.; Keyword: Dentistry.